1991
DOI: 10.1161/01.cir.83.6.2021
|View full text |Cite
|
Sign up to set email alerts
|

Beta-blocker treatment of dilated cardiomyopathy. Beneficial effect of carteolol in mice.

Abstract: BACKGROUND The effects of carteolol, a nonselective beta-adrenergic receptor blocker with intrinsic sympathomimetic activity, were compared with those of metoprolol in a murine model of viral myocarditis and dilated cardiomyopathy caused by encephalomyocarditis virus. METHODS AND RESULTS In the acute experiment, BALB/c and DBA/2 mice were inoculated with encephalomyocarditis virus. BALB/c mice were then given carteolol at 1 (n = 10), 10 (n = 10), 30 (n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0
2

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(20 citation statements)
references
References 48 publications
1
17
0
2
Order By: Relevance
“…31 The use of nonsteroidalantiinflammatory drugs was associated with increased mortality. 32,33,34 Taken together, these data support the application of the current heart-failure guidelines to patients with heart failure from myocarditis.…”
Section: Treatmentsupporting
confidence: 65%
“…31 The use of nonsteroidalantiinflammatory drugs was associated with increased mortality. 32,33,34 Taken together, these data support the application of the current heart-failure guidelines to patients with heart failure from myocarditis.…”
Section: Treatmentsupporting
confidence: 65%
“…A few studies have demonstrated beneficial effects of ␤-blockers in viral myocarditis. Tominaga et al (36) reported that the ␤-blocker carteolol had beneficial effects on dilated cardiomyopathy induced by EMCV but had no effect on the early stage of myocarditis. Nishio et al (30) reported that carvedilol improved the survival of mice infected with EMCV.…”
mentioning
confidence: 99%
“…An α-adrenergic blocking agent, and a β-adrenergic agent did not have a beneficial effect on the same animal model of viral myocarditis (Matsumori 1993;Tominaga et al 1991). Therefore, left ventricular unloading did not reduce myocardial injury.…”
Section: Discussionmentioning
confidence: 95%